Socio-economic analysis of open pollinated improved and hybrid maize production in Sindhupalchok district of Nepal - Tiwari, Grace; K.C., Chandan; Thapa, Praseed; Shrestha, Astha (Journal of Agriculture and Natural Resources, 2021)
The study was conducted from April to June, 2020 for comparative analysis of socioeconomic factors and profitability between Open Pollinated Improved (OPI) varieties and Hybrid varieties on maize production in Sindhupalchok district of Nepal. A structured questionnaire was administered to 80 randomly selected households i.e. 48 HHs cultivated OPI and 32 HHs cultivated hybrid maize varieties. Descriptive statistics, unpaired t-test, multiple linear regressions and indexing were used for data analysis using statistical tools- SPSS version 25 and MS-Excel. Linear regression model revealed that area under maize (5% level), education (5% level), age of household head (1% level), training (1% level), access to credit (5% level) and choice of seed (1 % level) significantly influenced maize production. In addition, unpaired t-test revealed that the productivity of hybrid maize varieties was significantly higher (1% level) than OPI varieties. Fall Armyworm infestation was found to more severe in OPI varieties (5% level) than hybrid. Furthermore, B: C ratio of hybrid varieties (1.59) indicated hybrid maize to be more profitable than OPI (1% level). However, the total cost of cultivation along with the cost of seed per hectare of OPI was found to be lower than hybrid varieties (1% level) thereby significantly increasing the area under maize production for OPI varieties (1% level). Indexing identified- lack of availability of quality seeds and fertilizers (I= 0.78) as the major problem associated with maize production. Ensuring access to quality seeds and fertilizer at subsidy, mechanization and efficient extension services focused on development of affordable hybrid maize varieties or high yielding OPI and its adoption among the farmers in order to increase maize productivity is recommended.